Pengaruh Pola Makan Gizi Seimbang Terhadap Kejadian Stunting pada Balita : Literatur Review - Daratullaila; Agrina Agrina; Erika Erika (Universitas Pahlawan Tuanku Tambusai, 2025)
Introduction: Stunting is a growth disorder in toddlers caused by chronic malnutrition and recurrent infections. According to WHO data from 2022, Indonesia ranks fifth among countries with the highest number of stunting cases in the world. Social and economic factors, as well as feeding practices, are the main causes of stunting in toddlers. Objective: This literature review aims to examine the influence of balanced dietary patterns on the incidence of stunting in toddlers. Methods: The databases used include Google Scholar, PubMed, ScienceDirect, and ResearchGate. The keywords used were stunting, toddler, and dietary pattern. A total of seven relevant articles were obtained through literature searching. The selection process involved screening based on the PICO elements and the CRAAP method. Results: Inappropriate feeding practices were significantly associated with the incidence of stunting. Factors such as food type, feeding frequency, and parental involvement in feeding contributed to children's growth status. Additionally, younger maternal age, low socioeconomic status, and failure to meet recommended nutritional intake were also found to increase the risk of stunting. Conclusion: Stunting prevention should focus on healthy eating patterns, appropriate meal schedules, and adequate nutritional intake for toddlers. Parental education and collaboration between the government, community, and health sectors are essential to improve understanding of balanced nutrition and reduce stunting prevalence